2005
DOI: 10.1002/bem.20105
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysiological responses of human volunteers to whole body RF exposure at 220 MHz

Abstract: Since 1994, our research has demonstrated how thermophysiological responses are mobilized in human volunteers exposed to three radio frequencies, 100, 450, and 2450 MHz. A significant gap in this frequency range is now filled by the present study, conducted at 220 MHz. Thermoregulatory responses of heat loss and heat production were measured in six adult volunteers (five males, one female, aged 24-63 years) during 45 min whole body dorsal exposures to 220 MHz radio frequency (RF) energy. Three power densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…At these very low levels, temperature considerations are likely to be meaningless [Adair et al, 2005]. At these very low levels, temperature considerations are likely to be meaningless [Adair et al, 2005].…”
Section: Exposure To Base Stations Compared To Other Rf Sourcesmentioning
confidence: 99%
“…At these very low levels, temperature considerations are likely to be meaningless [Adair et al, 2005]. At these very low levels, temperature considerations are likely to be meaningless [Adair et al, 2005].…”
Section: Exposure To Base Stations Compared To Other Rf Sourcesmentioning
confidence: 99%
“…The parameters of the RF field used in our studies is a 13.56‐megahertz (MHz) frequency and generates power ranging from 100 to 900 watts (approximately 1 kiloelectron volt‐20 kiloelectron volts/m 2 ). Electromagnetic energy produced in shortwave frequencies has a low tissue‐specific absorption rate and therefore has excellent whole‐body penetration with documented safety in humans . However, the question of what molecular changes RF treatment can stimulate inside cells and whether they diverge between normal and malignant cells remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…As in the previous model, our study was based on a generic model of the coil and the truncation of the head model at the neck did not allow realistic modeling of the full length for the DBS implant, usually connected to a stimulator placed on the clavicle. This study showed the computed electric field and SAR during MRI in tissues surrounding a DBS implant and did not include information about temperature, which depends on SAR as well as thermal properties of tissues and thermoregulatory mechanisms of the body [72]. A thermal analysis was beyond the scope of this work, which focused on quantifying the influence of the spatial resolution on the modeling of the electric field and inform decision-making with respect to low versus high resolution modeling.…”
Section: Discussionmentioning
confidence: 99%